Construction of heteroatom-doped and three-dimensional graphene materials for the applications in supercapacitors: A review - Li, Zesheng; Lin, Jiaping; Li, Bolin; Yu, Changlin; Wang, Hongqiang; Li, Qingyu (Journal of energy storage, 2021)
•Heteroatom-doped and three-dimensional (3-D) graphene materials have unique advantages.•Preparation methods of heteroatom-doped 3-D graphene materials are systematically reviewed.•Structural advantages of 3-D graphene foams and 3-D graphene powders materials are analyzed.•Designing theories of single-doped, double-doped, and triple-doped graphene are summarized.•Abundant case studies of single or multiple doped 3-D graphene for supercapacitors is provided. Supercapacitor is a promising energy storage device with the advantages of fast response to electrochemical process, long service life and high-power density. Scientists in the world have devoted a lot of efforts to the development of electrode materials with high stability and high capacity. Functionalized nanostructured carbon materials have attracted much attention and become the key electrode materials for energy storage in high-performance supercapacitors. Among various structures, the heteroatom-doped and three-dimensional (3-D) graphene materials have unique advantages. The heteroatom-doped structure provides many active sites for electrochemical reaction, and the three-dimensional structure promotes the ion transfer in the electrochemical process. In this review, the preparation methods of heteroatom-doped 3-D graphene materials and their applications in supercapacitors are systematically reviewed, including the preparation methods of heteroatom-doped graphene, the preparation methods of 3-D graphene materials, as well as the designing principles and case analyses of single-doped, double-doped, and triple-doped graphene in the application of supercapacitors. This review aims to provide theoretical guidance for the design, preparation, and performance optimization of heteroatom-doped 3-D graphene materials for the practical application of supercapacitors in the future. The synthesis methods, electrochemical performances, and capacitance mechanisms of heteroatom-doped 3-D graphene are systematically summarized. [Display omitted]